ATP and cough reflex hypersensitivity: a confusion of goals?. Issue 1 (6th July 2017) - Fowles, Helen Elizabeth; Rowland, Tim; Wright, Caroline; Morice, Alyn
We thank our friends M.G. Belvisi and J.A. Smith for their interest in our article. We are in agreement that cough hypersensitivity syndrome (CHS) is a clinical diagnosis, currently without a firm pathophysiological explanation. The exquisite sensitivity of patients with CHS to a wide variety of irritants is attested in every clinic and is a cardinal feature of the clinical history of this condition. The stunning effectiveness of AF-219/MK-7264 in chronic cough led us to the assumption that ATP inhalation may well be the physiological tool to define CHS just as methacholine hyperresponsiveness is useful in defining the phenomenon of bronchial hyperresponsiveness. Sadly, our results did not confirm this expectation. Our patients were not "uncharacterised" but had been through our well-established clinic protocol. They were entirely typical of chronic cough patients. The failure of ATP challenge to demonstrate a marked leftward shift in the concentration response curve in chronic cough is puzzling, but we have difficulty understanding M.G. Belvisi and J.A. Smith's alternative explanation. AF-219/MK-7264 is thought to have a mainly peripheral activity; however, the periphery will also include the nodose and jugular ganglia of the vagus nerve, where phenotypic switching has been well described [1]. Our observation that hypersensitivity in chronic cough was no more demonstrated by ATP than citric acid or capsaicin does, to us, suggest that this phenomenon resides not on the nerve terminals where we had for many years assumed it to be, but rather be part of a pan-neuronal phenomenon. Cough hypersensitivity is a mystery that continues to require unravelling http://ow.ly/Fhel30cgA5u